2006
DOI: 10.1002/jemt.20310
|View full text |Cite
|
Sign up to set email alerts
|

Composition of nasal airway surface liquid in cystic fibrosis and other airway diseases determined by X-ray microanalysis

Abstract: The ionic composition of the airway surface liquid (ASL) in healthy individuals and in patients with cystic fibrosis (CF) has been debated. Ion transport properties of the upper airway epithelium are similar to those of the lower airways and it is easier to collect nasal ASL from the nose. ASL was collected with ion exchange beads, and the elemental composition of nasal fluid was determined by X-ray microanalysis in healthy subjects, CF patients, CF heterozygotes, patients with rhinitis, and with primary cilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…In contrast, the Cl − concentration was significantly elevated in the CF samples (Supplemental Fig. S2), in agreement with a recent study [28]. Similarly, the NO 3 − concentration tended to be elevated in the ASL of CF patients compared to that of non-CF subjects (Supplemental Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, the Cl − concentration was significantly elevated in the CF samples (Supplemental Fig. S2), in agreement with a recent study [28]. Similarly, the NO 3 − concentration tended to be elevated in the ASL of CF patients compared to that of non-CF subjects (Supplemental Fig.…”
Section: Resultssupporting
confidence: 91%
“…A recent study also reported elevated Cl − in the nasal ASL of CF patients [28]; however, elevated Cl − levels were also found in the nasal ASL of non-CF patients with rhinitis [28]. Thus, increased Cl − concentration in the ASL may be a general sign of airway inflammation [28]. Our ASL analysis also revealed that the NO 3 − concentration tended to be elevated in the nasal secretions of CF subjects (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We also found that tracheal fluid in transgenic ∆F508-CFTR mice had a significantly higher content of Na and Cl than tracheal fluid in control mice [28] and that nasal fluid from CF-patients had a higher content of Na and Cl than nasal fluid of healthy controls, a difference that was in part due to the defective CFTR in CF-patients [29]. These findings are in line with studies by Reddy et al [30] and Kunzelmann et al [31] stating that activation of the epithelial Na + -channel (ENaC) requires activation of CFTR, hence in cultured CF cells, the activity of ENaC would be expected to be reduced.…”
Section: Discussionmentioning
confidence: 64%
“…In the one study that compared particle sizes from both healthy and infected individuals, 71 it was found that particles from infected individuals were larger than those from healthy individuals. Disease-induced changes, such as increases in mucus composition, quantity and viscosity, have also been observed, 2,117,118 which may suggest that the increase in size is directly related to increases in mucus viscosity. Differences in mucus composition at the mucuseair interface may be accountable for the inter-individual variability observed in studies of different respiratory activities.…”
Section: Mucus Propertiesmentioning
confidence: 99%